2016
DOI: 10.1161/jaha.116.003549
|View full text |Cite
|
Sign up to set email alerts
|

ABT‐719 for the Prevention of Acute Kidney Injury in Patients Undergoing High‐Risk Cardiac Surgery: A Randomized Phase 2b Clinical Trial

Abstract: BackgroundPatients undergoing cardiac surgeries with cardiopulmonary bypass (on‐pump) have a high risk for acute kidney injury (AKI). We tested ABT‐719, a novel α‐melanocyte‐stimulating hormone analog, for prevention of AKI in postoperative cardiac surgery patients.Methods and ResultsThis phase 2b randomized, double‐blind, placebo‐controlled trial included adult patients with stable renal function undergoing high‐risk on‐pump cardiac surgery in the United States and Denmark. Participants received placebo (n=61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
0
28
1
1
Order By: Relevance
“…8 This was a phase 2B study that was powered properly to test the hypothesis that there is a dose-dependent protective effect of ABT-719 on the development of AKI in high-risk patients 72 hours after surgery. This study built on promising data from a small, unpublished, single-dose study of ABT-719 in cardiac surgery patients.…”
Section: A Recent Therapeutic Failure In Akimentioning
confidence: 99%
See 4 more Smart Citations
“…8 This was a phase 2B study that was powered properly to test the hypothesis that there is a dose-dependent protective effect of ABT-719 on the development of AKI in high-risk patients 72 hours after surgery. This study built on promising data from a small, unpublished, single-dose study of ABT-719 in cardiac surgery patients.…”
Section: A Recent Therapeutic Failure In Akimentioning
confidence: 99%
“…10,15 The required patient enrollment was reached in this large, well-conducted, multicenter clinical study, but unfortunately the study showed no effect of ABT-719 on the primary (early AKI) or secondary end points (90 days >25% reduction in estimated glomerular filtration rate, or urinary or plasma AKI biomarkers). 8 In retrospect, it is notable that despite the strong supportive preclinical data, there were no published data indicating that MRs are expressed in human kidneys, or that there is aberrant activation of MSH/MR signaling in human kidneys after AKI. Another concern is that although published preclinical data in a variety of species from different laboratories have indicated that AP214 and α-MSH are protective after IR-induced AKI, 10,1618 it is not clear that IR injury is the mechanism of AKI after cardiac surgery with modern cardiopulmonary bypass machines.…”
Section: A Recent Therapeutic Failure In Akimentioning
confidence: 99%
See 3 more Smart Citations